Strengthening Soft Skills Through Character Education Based On Religious Values In Vocational High Schools - Dede Taufik N; Yani Mulyani; Muhamad Roikhan; Ai Wasliyah; Yeni Heryani; Dede Aji Mardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The motto of Vocational High School (SMK) known as SMK can, is interpreted that vocational school graduates can work in industry or the world of work, can continue their studies at university and can be entrepreneurs, or what is widely known as BMW. This study uses a qualitative approach with a descriptive type of research, to describe the development of soft skills through character education programs in the learning system in Vocational High Schools (SMK). The vocational schools that were used as the object of research were SMKN 1, SMKN 2, SKMN 3 AND SMKN 4. In order to instill character education in students, a set of program forms are needed, which are contained in the Education Unit Curriculum (KSP), as for its form; in the form of curriculum structure, curriculum content, integration in subjects, school culture and in the learning process. Each form of program has a function and meaning in order to shape the character and personality of students that leads to the development of soft skills. From the analysis of the data, it can be said that the ability of students' soft skills can develop well through several character education programs. The programs that are the levers for success in developing soft skills are memorizing and reading the Quran, weekly recitations/cults, Istighosah, Asmaul Husna Reading, Habituation of Dhuha Prayer and Mandatory Prayer, Botram (eating together, holding a National Event with the theme of education, morals and health.